Post-plasma-catalytic degradation of toluene using atmosphere double dielectric barrier discharge combined MnOx-based catalysts. Issue 3 (1st February 2021) - Zhang, Shuo; Liang, Jiyan; Yu, Xinyang; Xu, Tao; Shen, Xinjun
Abstract: Post-plasma catalytic system with Mn-based has shown potential performance in terms of air pollution degradation, in which Ce was induced into MnOx/Al2 O3 mixed with 1:1 weight ratio by the impregnation method to increase the capacity of toluene degradation. The catalytic ability of prepared catalysts was analyzed by characterizations of XRD, SEM, XPS, and BET. The effects of the SIE and initial concentration on toluene and CO2 production were discussed in this work. The results showed that the toluene removal efficiency and CO2 selectivity increased with the promotion of SIE. With the addition of 15% Ce1Mn1/A2 O3, the PPC system displayed the potential performance in the enhancement of toluene conversion and CO2 generation, and suppression of ozone and NO2 compared with plasma alone. At the SIE level of 504 J/L, the system showed better performance in terms of toluene removal efficiency (90.1%), CO2 selectivity (67.3%), O3 suppression (79.3%), and NO2 prohibition (61.8%). Also, the organic by-products generated by the PPC system were discussed. Graphical Abstract: